Posttraumatic chronic ossified extradural hematoma - Rakesh Kumar; Radhe Shyam Mittal (Romanian Neurosurgery, 2014)
Posttraumatic Chronic ossified extradural hematomas are rare entities. Natural absorption of EDH does not occurs due to calcification. Chronic ossified EDH is frequently present in paediatric age group. Careful regular follow-up is mandatory in conservatively managed case of EDH in children. We report a rare case of Posttraumatic Chronic ossified extradural hematomas in a 10-years old girl presenting six years after head injury with right temporal region swelling.